ANALISIS PENGARUH VARIABEL MODERASI SWITCHING COSTS TERHADAP HUBUNGAN SERVICE PERFORMANCE DAN CUSTOMER LOYALTY MEMBER CELEBRITY FITNESS JAKARTA - Bryan Bryan; Eddy Haryadi (Jurnal Manajemen, 2018)
The purpose of this research to determine the effect of moderating variables on the relationship between Switching Costs, Service Performance and Customer Loyalty among Celebrity Fitness members. This research was carried out in a service company Celebrity Fitness. The respondents were limited to the members of Celebrity Fitness in Jakarta. Data obtained by distributing questionnaires to the sample. The method used in sampling is simple random sampling by means of draws. The sample are 165 active members of Celebrity Fitness. The results showed that there is significant influence of the moderating variable on the relationship between Service Performance and Customer Loyalty. The results also show the Service Performance as an independent variable has a significant effect on customer loyalty. Switching Costs serves as a quasi moderator (serves as the independent variable and moderation) significantly affects customer loyalty and has a significant influence as a moderating variable in the relationship between Service Performance and Customer Loyalty.